2002
DOI: 10.1103/physrevlett.88.205505
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Carbon Nanotubes Filled withC60,CH4, or Ne: Predictions from Molecular Dynamics Simulation

Abstract: The effect of filling nanotubes with C60, CH4, or Ne on the mechanical properties of the nanotubes is examined. The approach is classical molecular dynamics using the reactive empirical bond order (REBO) and the adaptive intermolecular REBO potentials. The simulations predict that the buckling force of filled nanotubes can be larger than that of empty nanotubes, and the magnitude of the increase depends on the density of the filling material. In addition, these simulations demonstrate that the buckling force o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
113
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(124 citation statements)
references
References 45 publications
11
113
0
Order By: Relevance
“…Wang et al [11,12] studied elastic buckling of individual MWNTs under external radial pressure and axially compressed buckling of pressured MWNTs using a multiple-shell model. Their results showed that the predicted critical pressure and the predicted increment of critical axial stress due to an internal radial pressure using continuum mechanics model were in reasonably good agreement with the experiment results [13] and the results for filled CNTs by molecular dynamics simulations [14], respectively. Wang et al [15] studied the effect of van der Waals forces on the pull-in stability of CNTs using the cantilever beam with large deformation model.…”
Section: Introductionsupporting
confidence: 70%
“…Wang et al [11,12] studied elastic buckling of individual MWNTs under external radial pressure and axially compressed buckling of pressured MWNTs using a multiple-shell model. Their results showed that the predicted critical pressure and the predicted increment of critical axial stress due to an internal radial pressure using continuum mechanics model were in reasonably good agreement with the experiment results [13] and the results for filled CNTs by molecular dynamics simulations [14], respectively. Wang et al [15] studied the effect of van der Waals forces on the pull-in stability of CNTs using the cantilever beam with large deformation model.…”
Section: Introductionsupporting
confidence: 70%
“…It means that by inserting SWCNT into other CNTs with a larger diameter, the buckling capacity of the MWCNTs can be enhanced significantly. This point was also highlighted by Ni et al 32 in their MD simulations of SWCNTs filled with C 60 , CH 4 , or Ne and by Wang et al 33 in their analysis of axially compressed MWCNTs modeled by multiple continuum thin cylindrical shells. This characteristic of MWCNTs makes them promising candidates as superfibers for nanotube-composite materials.…”
Section: A Buckling Of Set 1 Mwcntsmentioning
confidence: 66%
“…The revised REBO realistically describes the properties of molecular and solidstate carbon materials, including bond energy, bond lengths, and lattice constant. 15 Hitherto the REBO potential has been widely used in the analysis of CNTs 18,[22][23][24][25][26][27][28][29][30][31] and has been proved to furnish reliable results when compared to the more accurate but computationally expensive tight-binding 32,33 or ab initio DFT methods. 34,35 In the MD simulations, the fifth-order Gear's predictorcorrector integration scheme is employed with a time step size of 1 fs.…”
Section: Computational Modelmentioning
confidence: 99%